2018
DOI: 10.3889/oamjms.2018.141
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Maximum Bite Force in Patients with Complete Dentures

Abstract: OBJECTIVE:This study aimed to evaluate maximum bite forces (mBF) in dominant (DS) and non-dominant sides (NDS) at certain time periods after the insertion of new complete dentures based on prior experience and gender.MATERIALS AND METHODS:A total of 88 patients, complete denture wearers (CDWs), were examined. The maximum bite force at the intercuspal position between the first molars in 3 seconds was registered and recorded with piezoelectric gnathodynamometer. The procedure was repeated 3 times in identical c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…In addition, our results indicate a significant (25.6%) difference in BF between the dominant-and non-dominant side of CCD wearers. Even more pronounced differences were recently reported by Shala et al (22), who found a BF in CCD users that was 80% lower in the non-dominant side. These authors attributed this difference to the individual preference for unilateral chewing, which contributes to muscle tonicity improvements and consequently results in greater BF (22).…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…In addition, our results indicate a significant (25.6%) difference in BF between the dominant-and non-dominant side of CCD wearers. Even more pronounced differences were recently reported by Shala et al (22), who found a BF in CCD users that was 80% lower in the non-dominant side. These authors attributed this difference to the individual preference for unilateral chewing, which contributes to muscle tonicity improvements and consequently results in greater BF (22).…”
Section: Discussionmentioning
confidence: 60%
“…The final reported value was calculated as the average of the 3 measurements. The sides with the highest and lowest BF values are hereafter referred to as the dominant side and non-dominant side, respectively (22).…”
Section: Bite Forcementioning
confidence: 99%
“…At the same time, studies show that the maximum force value in these patients varies according to the moment of recording relative to the moment of complete denture's application. Thus, even if this force has low initial value, some studies show a considerable increase after a period of 6 months [17], while other after a period of 7 weeks [18] from the application of the complete denture, as a result of patients' adaptation to the prostheses [18]. However, the value of the masticatory force remains lower than in dental subjects, by 20%-40% [17].…”
Section: Resultsmentioning
confidence: 98%
“…Okamoto, in 2012, finds an average value of 412.61N in complete denture patients [16]. Studies show that, from the point of view of localization, maximal masticatory force is developed in the first molar area [17][18], and it is also considered that 80% of the total masticatory force is distributed here. Taking into account the results of these researches, in our study the forces were applied in the first molar area, one of the purposes being to determine if the acrylic resin from which the complete denture is made can resist to the usual maximum forces exerted during mastication.…”
Section: Resultsmentioning
confidence: 99%
“…Naïve mice showed apparently increased bite force during repeated weekly testing, which may be related to the habituation or adaptation to the test as training can improve biting efficiency [10,12]. Similarly, the maximum bite force in patients with complete dentures increases during repeated testing [55]; and repeated exercises of the masticatory muscles can reduce muscle pain and fatigue [56]. In patients of first bite syndrome, pain triggered by the first bite of a meal improves in the subsequent bites [57,58].…”
Section: Injury Pain and Bite Forcementioning
confidence: 99%